PENERAPAN HUKUM PIDANA TERHADAP PENCUCIAN UANG DALAM TINDAK PIDANA KEJAHATAN NARKOTIKA (Putusan Mahkamah Agung Nomor 250 K/Pid.Sus/2018) - Manalu, Arisman Freddy; Purba, Nelvitia; Affan, Ibnu (Jurnal Ilmiah METADATA, 2021)
The crime of money laundering as a crime has a distinctive feature, namely that this crime is not a single crime but a multiple crime. The crime of money laundering does not stand alone because the assets placed, transferred, or transferred by means of integration are obtained from a criminal act, meaning that there has been another criminal act that preceded it. The formulation of the problem in this thesis is how to regulate the crime of money laundering, how to apply the law of money laundering in narcotics crime cases, how the legal basis for judges to return the assets of the defendant in the Supreme Court decision Number 250 K / Pid.Sus / 2018. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the regulation of money laundering in case Number 250 K / Pid.Sus / 2018 is regulated in Article 3 of Law Number 8 of 2010. Murtala Ilyas Bin Ilyas was legally and convincingly proven guilty of committing the crime of money laundering and imposing a crime. to the defendant with imprisonment for 8 (eight) years and a fine of Rp. 5,000,000,000.00 (five billion rupiah) provided that if the fine is not paid, then it is replaced by imprisonment for (three) months. The legal consideration of the judge returning the defendant's assets was because the evidence was obtained between 2002 and 2006, namely the period before the tempus delicti of 2009 to 2016, so the evidence had to be returned to the defendant Murtala Ilyas.